Time-dependent Picosecond Transient Absorption Spectra of 9-Acetylanthracene, Benzophenone and Acridine in Solution. Issue 1 (1984) - Hamanoue, Kumao; Nakajima, Kazuo; Hidaka, Toshiharu; Nakayama, Toshihiro; Teranishi, Hiroshi
Abstract : The transient absorption spectra of the title compounds in solutions at room temperature have been measured on the picosecond time scale. For 9-acetylanthracene and acridine there were measurable changes of the spectral shapes in the first picosecond region, while no spectral change was observed for benzophenone.